Sociolinguistic characteristics of the nominals in the Spanish spoken by Ashaninkan immigrants - Falcón Ccenta, Pedro (2014)
The characteristics of nominal-most recurrent structures of Spanish spoken by bilingual Ashaninka immigrants in Lima city are described from a functional sociolinguistic perspective. The evaluation of Noun Phrase (NP) structures are fundamentally studied under qualitative support in order to evaluate the sociolinguistic factors such as, age sex, schooling and time of residence, and the influence of the mother tongue when building up such structures. As we have observed, one of the forms which reproduce the native language is the elision of the article because in this language the determinative category is not present in a phonological form. In the focus of the nominal structures, the variable “time of residence” acquires more importance in simple NP that are involved in process of elision, discordance, double possessive, among others. However, the degree of schooling becomes less important as a factor of influence.